In the name of the residents' wellbeing: development of halal tourism in Indonesia using the “place attachment” approach and “value-belief-norm theory” - Dewi, Ike Janita (Frontiers in Sustainable Tourism, 2023)
Studies on halal tourism tend to be demand-side oriented. This paper offers an insight into halal tourism from the supply-side perspective using Place Attachment and Value-Norm-Belief. The study has two aims. The first aim is to develop a research model for the development of halal tourism from a supply-side perspective (i.e., using the perspective of residents living in the Special Region of Yogyakarta, Indonesia). The second aim is to formulate strategies and policies based on the results. Data were collected from the survey questionnaire of 251 respondents and analyzed using Descriptive Analysis and Partial Least Square Structural Equation Modeling (PLS-SEM). The findings showed that Place Dependence and Place Identity fully mediate the Perceived Benefits and Perceived Concerns on Attitudes toward halal tourism development. Perceived benefits positively affect attitude toward halal tourism development, whereas perceived concerns has negative affect. This study enriches tourism research by combining two concepts of Place Attachment and Value-Norm-Belief in the context of halal tourism. The empirical contribution of this research is the development of a model that can be applied in other regions.